Integrated Analyses Reveal the Multi-Omics and Prognostic Characteristics of ATP5B in Breast Cancer - Liu, Min; Xu, Yuxuan; Zhou, Yaoyao; Lang, Ronggang; Shi, Zhenyu; Zhao, Jing; Meng, Yuanyuan; Bao, Li (Frontiers in Genetics, 2021)
The beta subunit of F1Fo-ATP synthase (ATP5B) has been demonstrated to play an essential role in tumor progression and metastasis. However, there has been no integral genomic analysis of ATP5B in pan-cancer. Also, the clinical relevance of ATP5B and its potential mechanism in regulating breast cancer are still poorly understood. In this study, we found ATP5B had a higher frequency of amplification than deletion in most cancer types, and the copy number variation (CNV) of ATP5B had a significant positive correlation with the expression level of BRCA. DNA methylation analysis across pan-cancer revealed a strong correlation between ATP5B expression and epigenetic changes. We identified 6 significant methylation sites of ATP5B involved in the regulation of expression. Tissue microarrays (TMA) from 129 breast cancer samples were used to evaluate the expression of ATP5B and its correlation with prognosis. ATP5B mRNA expression and protein levels in breast cancer were significantly up-regulated compared with adjacent normal tissues. Higher levels of ATP5B expression were associated with a worse OS in patients with breast cancer. In addition, Cox regression analysis showed that ATP5B expression was an independent prognostic factor. Gene enrichment analysis indicated that the gene signatures of DNA damage recognition, the E-cadherin nascent pathway and the PLK1 pathway were enriched in ATP5B-high patients. Moreover, somatic mutation analysis showed that a significant mutation frequency of CDH1 and ADAMTSL3 could be observed between the ATP5B-high and ATP5B-low groups. In conclusion, this study has revealed significant and novel information regarding the genomic characteristics of ATP5B and it has highlighted the clinical value of ATP5B in predicting the outcome of breast cancer patients.